Tarzan & Dr. Moreau vs the subhumans & the Vodoo Zombies: colonialist and anti-colonialist discourses in pre-code hollywood (1932-1934) - Aragón, Alfonso M. Rodríguez de Austria Giménez de (Media & Jornalismo, 2016)
In this paper I analyse the implicit discourse about colonialism in six Hollywood films of the early thirties. That is, filmed before the hegemonic discourse supported by the censorship of the Production Code Administration was definitively imposed in 1934. The tour begins with Tarzan, guardian of the African colonies, and ends with Dr. Moreau in Island of Lost Souls, a film that Australian aborigines were forbidden to see.